Effects of Inflammatory Cell Death Caused by Catheter Ablation on Atrial Fibrillation - Liu D; Li Y; Zhao Q (Dove Medical Press, 2023)
Dishiwen Liu,1- 3,* Yajia Li,1- 3,* Qingyan Zhao1- 3 1Department of Cardiology, Renmin Hospital of Wuhan University, Wuhan, 430060, People's Republic of China; 2Cardiovascular Research Institute, Wuhan University, Wuhan, 430060, People's Republic of China; 3Hubei Key Laboratory of Cardiology, Wuhan, 430060, People's Republic of China*These authors contributed equally to this workCorrespondence: Qingyan Zhao, Department of Cardiology & Cardiovascular Research Institute Renmin Hospital of Wuhan University, 238 Jiefang Road, Wuchang District, Wuhan, Hubei, 430060, People's Republic of China, Tel +86- 027 88041911, Fax +86- 027 88042292, Email ruyan71@163.comAbstract: Atrial fibrillation (AF) poses a serious healthcare burden on society due to its high morbidity and the resulting serious complications such as thrombosis and heart failure. The principle of catheter ablation is to achieve electrical isolation by linear destruction of cardiac tissue, which makes AF a curable disease. Currently, catheter ablation does not have a high long-term success rate. The current academic consensus is that inflammation and fibrosis are central mechanisms in the progression of AF. However, artificially caused inflammatory cell death by catheter ablation may have a significant impact on structural and electrical remodeling, which may affect the long-term prognosis. This review first focused on the inflammatory response induced by apoptosis, necrosis, necroptosis, pyroptosis, ferroptosis and their interaction with arrhythmia. Then, we compared the differences in cell death induced by radiofrequency ablation, cryoballoon ablation and pulsed-field ablation. Finally, we discussed the structural and electrical remodeling caused by inflammation and the association between inflammation and the recurrence of AF after catheter ablation. Collectively, pulsed-field ablation will be a revolutionary innovation with faster, safer, better tissue selectivity and less inflammatory response induced by apoptosis-dominated cell death.Keywords: atrial fibrillation, inflammatory cell death, radiofrequency ablation, cryoballoon ablation, electroporation